Preparation method of nano-catalyst based on bimetal organic framework material as well as product and application of nano-catalyst
By partially replacing the Ce/Zr-UiO-66 material at the Zr site at the UiO-66 node, an efficient nanocatalyst was prepared, which solved the problem of low conversion of CO2 hydrogenation to methane at low temperatures, achieved high selectivity and high yield catalytic effects, and demonstrated good stability.
Patent Information
- Application Number
- CN202411728459.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-28
AI Technical Summary
The conversion rate of existing catalysts to catalyze CO2 hydrogenation to methane at low temperatures is relatively low, and the active interface structure of the catalyst is lacking in-depth understanding.
Using bimetallic organic frame material Ce/Zr-UiO-66 as a support, the Zr site part is replaced by Ce in the Zr6O8 cluster at the UiO-66 node by a one-pot method, and the ultra-small nanometals are anchored, thereby preparing an efficient nanocatalyst.
The hydrogenation of CO2 at low temperature 250°C showed a methane-selectivity of nearly 100% and a methane spatiotemporal yield of 338 mg h-1 kg cat-1 or above. The catalyst has good stability, and the catalytic activity and structure remain unchanged for 150 hours of continuous operation.
Smart Images

Figure CN119524928A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of carbon dioxide selective hydrogenation catalysts, and in particular to a preparation method of a nanocatalyst based on a bimetallic organic framework material, and a product and application thereof. Background Art
[0002] With the over-exploitation and burning of fossil energy, excessive carbon dioxide emissions have led to a series of increasingly severe environmental problems such as global temperature rise, ocean acidification, and extreme weather. At present, there is an urgent need to develop methods to effectively capture, store and convert large amounts of carbon dioxide (CCUS) to produce high value-added products such as methane, methanol and multi-carbon products, so as to re-apply carbon resources to related chemical fields and as a power source for new energy equipment, etc., to achieve a carbon closed loop in an environmentally friendly and economical way.
[0003] Methane, as the main component of natural gas, is a very important fuel resource for industrial production and human life. However, in modern society, it is often transported through large-scale mining and the construction of dense natural gas pipelines or high-end liquefied natural gas ships. Obviously, by capturing CO2 in situ near chemical plants such as coking plants, 2 Efficient conversion into methane can significantly reduce the cost of natural gas transportation. 2 Methanation catalysts are mainly nickel-based catalysts and ruthenium-based catalysts. Nickel-based catalysts are low-cost, but require higher temperatures to catalyze CO 2 Therefore, the development of efficient catalytic CO 2 Nickel-based catalysts for hydromethanation are an important research direction.
[0004] At present, a variety of strategies have been developed to improve the activity of existing catalysts. For example, CN118267996A designed a hollow nickel-cerium dioxide catalyst, using cheap silicon dioxide as a template, loading the active metal nickel on the outer layer, and finally coating and growing a layer of cerium dioxide and etching and reducing it to obtain a hollow catalyst Ni@CeO 2 , forming a strong metal-support interaction through a special structure. At the same time, the calcination temperature was studied and it was found that 650°C was the optimal calcination temperature. The prepared 15% Ni@CeO 2 -650 achieved a conversion rate of nearly 80% and a methane selectivity of more than 99% at 250°C. CN118719082A adds tungsten to Ni / γ-Al 2 O 3 The catalytic performance has been greatly improved by modification, and the conversion rate can be increased by about 40% under the same temperature reaction conditions.2 O 3 The addition of yttrium oxide to the carrier greatly improves the catalytic activity of the supported Ni nanoparticles at low temperatures. Under reaction conditions of 250°C, the methane selectivity is increased by 15% (reaching 99%), while CO 2 The conversion rate increased by about 60%. In terms of stability, the addition of yttrium oxide can adjust the number of basic sites in the catalyst and improve the catalyst's ability to resist carbon deposition. Even at 300°C, the 70-hour stability test can maintain 99% methane selectivity and 80% CO 2 Conversion rate.
[0005] As mentioned above, although various types of catalysts and modification methods have been reported, the catalytic conversion of CO 2 The low-temperature conversion rate of hydrogenation to methane is still low, and there is a lack of in-depth understanding of the precise active interface structure of the catalyst. Therefore, it is urgent to develop new and efficient catalysts, rationally design the catalytic interface, and achieve high conversion, high selectivity and long-term stable catalytic CO under mild conditions. 2 Hydrogenation to produce methane. Summary of the invention
[0006] In view of the deficiencies in the prior art, the object of the present invention is to provide a method for preparing a nanocatalyst based on a bimetallic organic framework material, and its product and application.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a nanocatalyst based on a bimetallic organic framework material, the preparation method comprising the following steps:
[0009] (1) 1,4-terephthalic acid and N,N-dimethylformamide are mixed to obtain solution A, solution A is mixed with formic acid, ammonium cerium nitrate, and zirconium oxynitrate, heated, centrifuged, dried, and activated to obtain a bimetallic organic framework material Ce / Zr-UiO-66;
[0010] (2) Mixing the metal salt precursor with the bimetallic organic framework material Ce / Zr-UiO-66, drying, and reducing to obtain the bimetallic organic framework material-based nanocatalyst.
[0011] The present invention synthesizes Zr at the UiO-66 node by a one-pot method. 6 O 8 The Zr sites in the cluster are partially replaced by Ce, and the ultra-small nano-metal is anchored. The synthesis method is easy to operate, and the active structure of the formed nano-metal can be precisely controlled by anchoring the framework itself. The catalyst provided by the present invention can catalyze CO at a low temperature of 250°C. 2The hydrogenation yielded methane and showed nearly 100% methane selectivity and 338 mg h -1 kg cat -1 The above methane space-time yield and catalytic performance are better than those of conventional supported Ni catalysts and single metal node MOF supported Ni catalysts. The catalyst provided by the present invention has good stability, and its catalytic activity and catalyst structure remain unchanged in a catalytic test of continuous operation for 150 hours.
[0012] Preferably, the ratio of the 1,4-terephthalic acid and the N,N-dimethylformamide in step (1) is (30-40) mg:1 mL, for example, 30 mg:1 mL, 31 mg:1 mL, 32 mg:1 mL, 33 mg:1 mL, 34 mg:1 mL, 35 mg:1 mL, 36 mg:1 mL, 37 mg:1 mL, 38 mg:1 mL, 39 mg:1 mL, 40 mg:1 mL, etc. Other specific point values within this numerical range can be selected and will not be described one by one here.
[0013] Preferably, the molar ratio of 1,4-terephthalic acid, zirconyl nitrate and ammonium cerium nitrate is (6-25):(5-19):1, wherein (6-25) can be selected from 6, 8, 10, 12, 14, 16, 18, 20, 21, 22, 23, 24, 25, etc., and (5-19) can be selected from 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, etc. Other specific point values within the above numerical range can be selected, and they will not be repeated here.
[0014] Preferably, the volume ratio of formic acid to N,N-dimethylformamide is 1:(3-4), for example 1:3, 1:3.1, 1:3.2, 1:3.3, 1:3.4, 1:3.5, 1:3.6, 1:3.7, 1:3.8, 1:3.9, 1:4, etc. Other specific point values within this numerical range can be selected and will not be described here one by one.
[0015] Preferably, the heating in step (1) is stirring heating.
[0016] Preferably, the heating temperature is 90-110°C (for example, 90°C, 92°C, 94°C, 96°C, 98°C, 100°C, 102°C, 104°C, 106°C, 108°C, 110°C, etc.), the heating time is 12-18min (for example, 12min, 13min, 14min, 15min, 16min, 17min, 18min, etc.), and other specific point values within the above numerical range can be selected, which will not be repeated here.
[0017] Preferably, the stirring speed is 500-1000rpm, for example, 500rpm, 550rpm, 600rpm, 650rpm, 700rpm, 750rpm, 800rpm, 850rpm, 900rpm, 950rpm, 1000rpm, etc. Other specific point values within this numerical range can be selected, which will not be described here one by one.
[0018] Preferably, the washing in step (1) comprises: re-dispersing the precipitate obtained after centrifugation in N,N-dimethylformamide and centrifuging it for 1-3 times (e.g., 1 time, 2 times, 3 times, etc.), and then dispersing it in acetone and centrifuging it for 2-4 times (e.g., 2 times, 3 times, 4 times, etc.). Other specific point values within the above numerical range can be selected and will not be described one by one here.
[0019] Preferably, the centrifugal speed in N,N-dimethylformamide is 8000-12000rpm (for example, 8000rpm, 8500rpm, 9000rpm, 9500, 10000rpm, 11000rpm, 12000rpm, etc.), and the centrifugal time is 10-20min (for example, 10min, 11min, 12min, 13min, 14min, 15min, 16min, 17min, 18min, 19min, 20min, etc.), and other specific point values within the above numerical range can be selected, which will not be repeated here.
[0020] Preferably, the centrifugal speed in acetone is 9000-13000 rpm (e.g., 9000 rpm, 9500, 10000 rpm, 11000 rpm, 12000 rpm, 12500 rpm, 13000 rpm, etc.), and the centrifugal time is 3-7 min (e.g., 3 min, 4 min, 5 min, 6 min, 7 min, etc.). Other specific point values within the above numerical range can be selected and will not be described one by one here.
[0021] Preferably, the drying temperature is 70-90°C (for example, 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C, 90°C, etc.), and the drying time is 10-14h (for example, 10h, 10.5h, 11h, 11.5h, 12h, 12.5h, 13h, 13.5h, 14h, etc.). Other specific point values within the above numerical range can be selected, and they will not be described one by one here.
[0022] Preferably, the activation temperature is 100-150°C (for example, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, etc.), and the activation time is 1-3h (for example, 1h, 1.5h, 2h, 2.5h, 3h, etc.). Other specific point values within the above numerical range can be selected, and they will not be described one by one here.
[0023] Preferably, the metal salt precursor in step (2) includes a nickel salt precursor, a palladium salt precursor, a platinum salt precursor or a ruthenium salt precursor.
[0024] The synthesis method provided by the present invention can be applied to the synthesis of small-sized precious metal nanoparticles such as nickel, palladium, platinum, ruthenium, etc. on metal organic framework materials.
[0025] Preferably, the nickel salt precursor comprises nickel nitrate hexahydrate.
[0026] Preferably, the mass ratio of the metal salt precursor and the bimetallic organic framework material Ce / Zr-UiO-66 is (1-2):(1-2), wherein (1-2) can be selected as 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, etc., and other specific point values within this numerical range can be selected, which will not be repeated here.
[0027] Preferably, the step (2) of mixing the metal salt precursor with the bimetallic organic framework material Ce / Zr-UiO-66 comprises: dropping the metal salt precursor aqueous solution into the bimetallic organic framework material Ce / Zr-UiO-66 dispersion under stirring.
[0028] Preferably, the metal salt precursor is mixed with the bimetallic organic framework material Ce / Zr-UiO-66 and stirred for 22-26 hours (for example, 22 hours, 23 hours, 24 hours, 25 hours, 26 hours, etc.). Other specific point values within this numerical range can be selected and will not be described one by one here.
[0029] Preferably, the drying in step (2) includes first evaporating to remove excess water and then drying.
[0030] Preferably, the evaporating comprises rotary evaporation.
[0031] Preferably, the temperature of the rotary evaporation is 50-90°C (for example, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, etc.), and other specific point values within this numerical range can be selected, which will not be described here one by one.
[0032] Preferably, the rotation speed of the rotary evaporation is 150-200 rpm (for example, 150 rpm, 160 rpm, 170 rpm, 180 rpm, 190 rpm, 200 rpm, etc.), and other specific point values within this numerical range can be selected, which will not be described one by one here.
[0033] Preferably, the pressure of the rotary evaporation is -0.6 to -1 atm (e.g., -0.6 atm, -0.7 atm, -0.8 atm, -0.9 atm, -1 atm, etc.), and other specific point values within this numerical range can be selected, which will not be described here one by one.
[0034] Preferably, the drying temperature is 60-100°C (for example, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, etc.), and the drying time is 10-14h (for example, 10h, 10.5h, 11h, 11.5h, 12h, 12.5h, 13h, 13.5h, 14h, etc.). Other specific point values within the above numerical range can be selected, and they will not be described one by one here.
[0035] Preferably, the reduction in step (2) comprises: heating reduction in a hydrogen atmosphere of 8%-12% (e.g., 8%, 9%, 10%, 11%, 12%, etc.), and other specific point values within this numerical range can be selected and will not be described in detail here.
[0036] Preferably, the heating reduction includes: heating to 220-280°C (e.g., 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, etc.) at 1-3°C / min (e.g., 1°C / min, 1.5°C / min, 2°C / min, 2°C / min, 2.5°C / min, 3°C / min, etc.) and reducing for 5-7h (e.g., 5h, 5.5h, 6h, 6.5h, 7h, etc.). Other specific point values within the above numerical range can be selected and will not be described one by one here.
[0037] In a second aspect, the present invention provides a nanocatalyst based on a bimetallic organic framework material prepared according to the preparation method described in the first aspect.
[0038] In a third aspect, the present invention provides a nanocatalyst based on a bimetallic organic framework material according to the second aspect in catalyzing CO 2 Application in hydrogenation to methane reaction.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] The present invention synthesizes Zr at the UiO-66 node by a one-pot method. 6 O 8The Zr sites in the cluster are partially replaced by Ce, and the ultra-small nano-metal is anchored. The synthesis method is easy to operate, and the active structure of the formed nano-metal can be precisely controlled by anchoring the framework itself. The catalyst provided by the present invention can catalyze CO at a low temperature of 250°C. 2 The hydrogenation yielded methane and showed nearly 100% methane selectivity and 338 mg h -1 kg cat -1 The above methane space-time yield and catalytic performance are better than those of conventional supported Ni catalysts and single metal node MOF supported Ni catalysts. The catalyst provided by the present invention has good stability, and its catalytic activity and catalyst structure remain unchanged in a catalytic test of continuous operation for 150 hours. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 is a scanning electron microscope image of Ce / Zr-UiO-66 synthesized in step (1) of Example 1;
[0042] Figure 2 This is a high magnification (×170000) transmission electron microscope image of Ni@Ce / Zr-UiO-66 synthesized in Example 1;
[0043] Figure 3 This is a high magnification (×250,000) transmission electron microscope image of Ni@Ce / Zr-UiO-66 synthesized in Example 1;
[0044] Figure 4 is a statistical diagram of the particle size of Ni@Ce / Zr-UiO-66 synthesized in Example 1;
[0045] Figure 5 is a high-angle annular dark-field scanning transmission electron microscopy image of Ni@Ce / Zr-UiO-66 synthesized in Example 1;
[0046] Figure 6 is the element distribution diagram of Ni@Ce / Zr-UiO-66 synthesized in Example 1;
[0047] Figure 7 is the XRD spectrum of Ce / Zr-UiO-66 synthesized in step (1) of Example 1;
[0048] Figure 8 is the XRD spectrum of Ni@Ce / Zr-UiO-66 synthesized in Example 1;
[0049] Fig. 9 is a catalytic stability data diagram of Ni@Ce / Zr-UiO-66 synthesized in Example 1 in Test Example 2;
[0050] Fig.10It is a high magnification (×170000) transmission electron microscope image of Ni@Ce / Zr-UiO-66 synthesized in Example 1 after the reaction in Test Example 2;
[0051] Fig.11 It is the XRD spectrum of Ni@Ce / Zr-UiO-66 synthesized in Example 1 after the reaction in Test Example 2. DETAILED DESCRIPTION
[0052] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0053] In the following examples, unless otherwise specified, the reagents and consumables used were purchased from conventional reagent manufacturers in the field; unless otherwise specified, the experimental methods and technical means used were conventional methods and means in the field.
[0054] Example 1
[0055] This embodiment provides a nano nickel catalyst Ni@Ce / Zr-UiO-66 based on a bimetallic organic framework material, and the preparation method is as follows:
[0056] (1) Synthesis of bimetallic organic framework material Ce / Zr-UiO-66:
[0057] The ligand 1,4-terephthalic acid (H 2 255.2 mg of BDC was dissolved in 7.2 mL of N, N-dimethylformamide (DMF) and transferred to a 15 mL thick-walled pressure bottle. Subsequently, 2.06 mL of formic acid (99%) was added, and finally 240 μL of 0.533 mol / L cerium ammonium nitrate aqueous solution and 2160 μL of 0.533 mol / L zirconium oxynitrate aqueous solution were added and mixed evenly. The pressure bottle was placed in an oil bath and heated at 100 ° C and stirred for 15 min at a speed of 800 rpm. After the synthesis, the glass reactor was cooled to 25 ° C and the precipitate Ce / Zr-UiO-66 was separated by centrifugation. After pouring out the mother liquor, the precipitate was redispersed in 6 mL of DMF and centrifuged three times (10000 rpm) for 14 min, followed by centrifugation in 6 mL of acetone three times (11000 rpm) for 5 min. Finally, the obtained Ce / Zr-UiO-66 was dried in a vacuum oven at 80 °C for 12 h and activated at 120 °C for 2 h.
[0058] (2) Synthesis of Ni@Ce / Zr-UiO-66:
[0059] 200 mg of nickel nitrate hexahydrate was dissolved in 5 mL of ultrapure water, and the solution was added dropwise to 45 mL of aqueous dispersion containing 200 mg of Ce / Zr-UiO-66 under stirring. After stirring for 24 hours, excess water was removed by a rotary evaporator, wherein the rotary evaporator was set to a temperature of 70 ° C, a speed of 175 rpm, and a pressure of -0.8 atm. After the rotary evaporation, it was placed in a vacuum oven at 80 ° C and dried for 12 hours. The obtained solid was further reduced to 250 ° C at 2 ° C / min for 6 hours in a tubular furnace under a 10% hydrogen and 90% argon atmosphere to obtain a nano-nickel catalyst Ni@Ce / Zr-UiO-66 based on a bimetallic organic framework material.
[0060] Example 2
[0061] This embodiment provides a nano nickel catalyst Ni@Ce / Zr-UiO-66 based on a bimetallic organic framework material, and the preparation method is as follows:
[0062] (1) Synthesis of bimetallic organic framework material Ce / Zr-UiO-66:
[0063] The ligand 1,4-terephthalic acid (H 2 255.2 mg of BDC was dissolved in 7 mL of N,N-dimethylformamide (DMF) and transferred to a 15 mL thick-walled pressure bottle. Subsequently, 2.3 mL of formic acid (99%) was added, and finally 120 μL of 0.533 mol / L aqueous solution of cerium ammonium nitrate and 2280 μL of 0.533 mol / L aqueous solution of zirconium oxynitrate were added and mixed evenly. The pressure bottle was placed in an oil bath and heated at 90 ° C and stirred for 18 min at a speed of 900 rpm. After the synthesis, the glass reactor was cooled to 25 ° C and the precipitate Ce / Zr-UiO-66 was separated by centrifugation. After pouring out the mother liquor, the precipitate was redispersed in 6 mL of DMF and centrifuged once (9000 rpm) for 20 min, followed by four centrifugations in 6 mL of acetone (10000 rpm) for 7 min. Finally, the obtained Ce / Zr-UiO-66 was dried in a vacuum oven at 85 °C for 11 h and activated at 110 °C for 2.5 h.
[0064] (2) Synthesis of Ni@Ce / Zr-UiO-66:
[0065] 200 mg of nickel nitrate hexahydrate was dissolved in 5 mL of ultrapure water, and the solution was added dropwise to 45 mL of aqueous dispersion containing 180 mg of Ce / Zr-UiO-66 under stirring. After stirring for 22 hours, excess water was removed by a rotary evaporator, wherein the rotary evaporator was set to a temperature of 60 ° C, a speed of 200 rpm, and a pressure of -1 atm. After the rotary evaporation, it was placed in a vacuum oven at 70 ° C and dried for 13 hours. The obtained solid was further reduced to 260 ° C at 3 ° C / min in a tubular furnace under a 10% hydrogen and 90% argon atmosphere for 5 hours to obtain a nano-nickel catalyst Ni@Ce / Zr-UiO-66 based on a bimetallic organic framework material.
[0066] Example 3
[0067] This embodiment provides a nano nickel catalyst Ni@Ce / Zr-UiO-66 based on a bimetallic organic framework material, and the preparation method is as follows:
[0068] (1) Synthesis of bimetallic organic framework material Ce / Zr-UiO-66:
[0069] The ligand 1,4-terephthalic acid (H 2 255.2 mg of BDC was dissolved in 7.5 mL of N,N-dimethylformamide (DMF) and transferred to a 15 mL thick-walled pressure bottle. Then 1.9 mL of formic acid (99%) was added, and finally 360 μL of 0.533 mol / L cerium ammonium nitrate aqueous solution and 2040 μL of 0.533 mol / L zirconium oxynitrate aqueous solution were added and mixed evenly. The pressure bottle was placed in an oil bath and heated at 110 ° C and stirred for 12 min at a speed of 700 rpm. After the synthesis, the glass reactor was cooled to 25 ° C and the precipitate Ce / Zr-UiO-66 was separated by centrifugation. After pouring out the mother liquor, the precipitate was redispersed in 6 mL of DMF and centrifuged three times (11000 rpm) for 10 min, followed by centrifugation twice (12000 rpm) in 6 mL of acetone for 3 min. Finally, the obtained Ce / Zr-UiO-66 was dried in a vacuum oven at 75 °C for 13 h and activated at 130 °C for 1.5 h.
[0070] (2) Synthesis of Ni@Ce / Zr-UiO-66:
[0071] 180 mg of nickel nitrate hexahydrate was dissolved in 5 mL of ultrapure water, and the solution was added dropwise to 45 mL of aqueous dispersion containing 200 mg of Ce / Zr-UiO-66 under stirring. After stirring for 26 hours, excess water was removed by a rotary evaporator, wherein the rotary evaporator was set to a temperature of 80 ° C, a speed of 150 rpm, and a pressure of -0.6 atm. After the rotary evaporation, it was placed in a vacuum oven at 90 ° C and dried for 11 hours. The obtained solid was further reduced to 240 ° C at 1 ° C / min in a tubular furnace under a 10% hydrogen and 90% argon atmosphere for 7 hours to obtain a nano-nickel catalyst Ni@Ce / Zr-UiO-66 based on a bimetallic organic framework material.
[0072] Comparative Example 1
[0073] This comparative example provides a nickel nanoparticle catalyst Ni@Zr-UiO-66 loaded on Zr-UiO-66, and the preparation method is as follows:
[0074] (1) Synthesis of metal organic framework material Zr-UiO-66:
[0075] The ligand 1,4-terephthalic acid (H 2 255.2 mg of BDC was dissolved in 7.2 mL of N,N-dimethylformamide (DMF) and transferred to a 15 mL thick-walled pressure bottle. Subsequently, 2.06 mL of formic acid (99%) was added, and finally 2.4 mL of an aqueous zirconium oxynitrate solution with a concentration of 0.533 mol / L was added and mixed evenly. The pressure bottle was placed in an oil bath and heated at 100 ° C and stirred for 15 min at a speed of 800 rpm. After the synthesis, the glass reactor was cooled to 25 ° C and the precipitate Zr-UiO-66 was separated by centrifugation. After pouring out the mother liquor, the precipitate was redispersed in 6 mL of DMF and centrifuged three times (10000 rpm) for 14 min, followed by centrifugation in 6 mL of acetone three times (11000 rpm) for 5 min. Finally, the obtained Zr-UiO-66 was dried in a vacuum oven at 80 ° C for 12 h and activated at 120 ° C for 2 h.
[0076] (2) Synthesis of Ni@Zr-UiO-66:
[0077] 200 mg of nickel nitrate hexahydrate was dissolved in 5 mL of ultrapure water, and the solution was added dropwise to 45 mL of aqueous dispersion containing 200 mg of UiO-66 under stirring. After stirring for 24 hours, excess water was removed by a rotary evaporator, wherein the rotary evaporator was set to a temperature of 70 ° C, a speed of 175 rpm, and a pressure of -0.8 atm. After the rotary evaporation, it was placed in a vacuum oven at 80 ° C and dried for 12 hours. The obtained solid was further reduced to 250 ° C at 2 ° C / min for 6 hours in a tubular furnace under a 10% hydrogen and 90% argon atmosphere to obtain a nano nickel catalyst Ni @ Zr-UiO-66 based on a bimetallic organic framework material.
[0078] Comparative Example 2
[0079] This comparative example provides a nickel nanoparticle catalyst Ni@Ce-UiO-66 loaded on Ce-UiO-66, and the preparation method is as follows:
[0080] (1) Synthesis of metal organic framework material Ce-UiO-66:
[0081] The ligand 1,4-terephthalic acid (H 2 255.2 mg of BDC was dissolved in 7.2 mL of N, N-dimethylformamide (DMF) and transferred to a 15 mL thick-walled pressure bottle. Subsequently, 2.06 mL of formic acid (99%) was added, and finally 2.4 mL of cerium ammonium nitrate aqueous solution with a concentration of 0.533 mol / L was added and mixed evenly. The pressure bottle was placed in an oil bath and heated at 100 ° C and stirred for 15 min at a speed of 800 rpm. After the synthesis, the glass reactor was cooled to 25 ° C and the precipitate Ce-UiO-66 was separated by centrifugation. After pouring out the mother liquor, the precipitate was redispersed in 6 mL of DMF and centrifuged three times (10000 rpm) for 14 min, followed by centrifugation in 6 mL of acetone three times (11000 rpm) for 5 min. Finally, the obtained Ce-UiO-66 was dried at 80 ° C for 12 h in a vacuum oven and activated at 120 ° C for 2 h.
[0082] (2) Synthesis of Ni@Ce-UiO-66:
[0083] 200 mg of nickel nitrate hexahydrate was dissolved in 5 mL of ultrapure water, and the solution was added dropwise to 45 mL of aqueous dispersion containing 200 mg of Ce-UiO-66 under stirring. After stirring for 24 hours, excess water was removed by a rotary evaporator, wherein the rotary evaporator was set to a temperature of 70 ° C, a speed of 175 rpm, and a pressure of -0.8 atm. After the rotary evaporation, it was placed in a vacuum oven at 80 ° C and dried for 12 hours. The obtained solid was further reduced to 250 ° C at 2 ° C / min for 6 hours in a tubular furnace under a 10% hydrogen and 90% argon atmosphere to obtain a nano nickel catalyst Ni@Ce-UiO-66 based on a bimetallic organic framework material.
[0084] Comparative Example 3
[0085] This comparative example provides a ZrO 2 Nickel nanoparticle catalyst Ni / ZrO 2 , the preparation method is as follows:
[0086] 200 mg of nickel nitrate hexahydrate was dissolved in 5 mL of ultrapure water, and the solution was added dropwise to 45 ml of aqueous dispersion in which 200 mg of commercial zirconium oxide (CAS No. 1314-23-4 manufactured by Aladdin) was dispersed under stirring. After stirring for 24 hours, excess water was removed by a rotary evaporator, wherein the rotary evaporator was set to a temperature of 70 ° C, a speed of 175 rpm, and a pressure of -0.8 atm. After the rotary evaporation was completed, it was placed in a vacuum oven at 80 ° C and dried for 12 hours. The obtained solid was further reduced by a tubular furnace in an atmosphere of 10% hydrogen and 90% argon at 2 ° C / min to 250 ° C for 6 hours to obtain a nickel nanoparticle catalyst Ni / ZrO 2 .
[0087] Test Example 1
[0088] This test example characterizes the structure of Ni@Ce / Zr-UiO-66 synthesized in Example 1:
[0089] (1) Scanning electron microscope test: The bimetallic organic framework material Ce / Zr-UiO-66 synthesized in step (1) of Example 1 was characterized using an ultra-high resolution cold field emission scanning electron microscope (Hitachi-SU8220). Figure 1 As shown, Ce / Zr-UiO-66 has an octahedral morphology with uniform size distribution and an average size of 50 nm.
[0090] (2) Transmission electron microscopy test: A field emission transmission electron microscope (Tecnai G2 F20U-TWIN) was used to characterize the morphology and distribution of the Ni@Ce / Zr-UiO-66 nanoparticles synthesized in Example 1. Figures 2 to 6As shown, in the synthesized catalyst Ni@Ce / Zr-UiO-66, Ni nanoparticles are uniformly distributed in the pores of Ce / Zr-UiO-66, with small and uniform size, an average particle size of 1.56 nm, and no obviously large-sized Ni nanoparticles are generated.
[0091] (3) Powder X-ray diffraction test: The prepared catalyst was characterized using an X-ray diffractometer (Rigaku D / MAX-TTRIII). Figure 7 , Figure 8 As shown, the Ce / Zr-UiO-66 synthesized in Example 1 has a good crystal structure. After the subsequent synthesis of Ni@Ce / Zr-UiO-66, the crystal structure remains unchanged and there is no characteristic peak of metallic Ni, which is attributed to the uniform distribution of Ni nanoparticles in the carrier and their small size.
[0092] Test Example 2
[0093] (1)CO 2 Hydrogenation solid phase catalytic test: 100 mg of the catalysts prepared in Examples 1-3 and Comparative Examples 1-3 were mixed with 1.8 g of quartz sand with a mesh size of 40-60 and then filled into a quartz glass reaction tube with an inner diameter of 9 mm. Both ends of the packing layer were fixed with quartz wool. 2 and CO 2 As the reaction gas, the mixing ratio is controlled to be H 2 :CO 2 The catalyst was activated by heating to 250 °C at a rate of 5 °C / min and the mass space velocity was 6000 mL g cat -1 h -1 , gas flow rate was 10 mg / min, catalytic CO 2 Hydrogenation test.
[0094] Each steady-state catalytic data was collected by a gas chromatograph (Shimadzu GC-2014C, Japan) equipped with two hydrogen flame ionization detectors (FID) and a thermal conductivity detector (TCD) after at least one day of stabilization, and the conversion rate, product space-time yield and selectivity were calculated based on the peak areas of carbon monoxide, methane and other peaks detected and combined with the standard curves of each substance. The catalytic results are shown in Table 1.
[0095] Table 1
[0096] Group <![CDATA[Methane space-time yield (g h -1 kg cat -1 )]]> Selectivity (%) Example 1 340.5 99.3 Example 2 338.6 98.7 Example 3 341.3 98.5 Comparative Example 1 193.6 98.8 Comparative Example 2 220.6 96.3 Comparative Example 3 189.6 97.6
[0097] It can be seen from Table 1 that the catalyst Ni@Ce / Zr-UiO-66 provided by the present invention has a high thermal conductivity of 338 g h at a low temperature of 250 °C. -1 kg cat -1The high methane space-time yield is above 98.5%, and the methane selectivity is above 98.5%. The Ni@Zr-UiO-66 synthesized in Comparative Example 1 shows a 193.6gh -1 kg cat -1 The methane space-time yield and selectivity of 98.8% are higher than that of Ni@Ce-UiO-66 synthesized in Comparative Example 2 and Ni / ZrO 2 At this temperature, it also has a certain methane space-time yield, but the selectivity is slightly lower. Specifically, compared with traditional supported catalysts and single metal node MOF-supported Ni catalysts, for catalytic CO 2 In the hydrogenation process to produce methane, the catalyst Ni@Ce / Zr-UiO-66 provided by the present invention exhibits great advantages of high yield and high selectivity under low temperature conditions.
[0098] (2) Stability test: Fig. 9 As shown, in the 150h catalytic test, the methane space-time yield of the catalyst Ni@Ce / Zr-UiO-66 provided in Example 1 of the present invention did not decay, and had good stability.
[0099] The Ni@Ce / Zr-UiO-66 catalyst of Example 1 was tested by transmission electron microscopy after 150 hours of catalytic testing. Fig.10 As shown, in the process of CO 2 After the hydrogenation catalytic reaction, the distribution and size of nano-Ni remain basically unchanged, without agglomeration and sintering.
[0100] The powder X-ray diffraction test of the Ni@Ce / Zr-UiO-66 catalyst in Example 1 after 150 hours of catalytic testing was performed. The results are as follows: Fig.11 As shown, in the CO 2 After the hydrogenation catalytic reaction, the catalyst crystal structure remains unchanged.
[0101] The applicant declares that the present invention illustrates the technical solution of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
[0102] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0103] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
Claims
1. A method for preparing a nanocatalyst based on a bimetallic organic framework material, characterized in that: The preparation method comprises the following steps: (1) 1,4-terephthalic acid and N,N-dimethylformamide are mixed to obtain solution A, solution A is mixed with formic acid, ammonium cerium nitrate, and zirconium oxynitrate, heated, centrifuged, dried, and activated to obtain a bimetallic organic framework material Ce / Zr-UiO-66; (2) Mixing the metal salt precursor with the bimetallic organic framework material Ce / Zr-UiO-66, drying, and reducing to obtain the bimetallic organic framework material-based nanocatalyst.
2. The preparation method according to claim 1, characterized in that: The ratio of the 1,4-terephthalic acid to the N,N-dimethylformamide in step (1) is (30-40) mg:1 mL; Preferably, the molar ratio of 1,4-terephthalic acid, zirconium oxynitrate and ammonium cerium nitrate is (6-25):(5-19):1; Preferably, the volume ratio of formic acid to N,N-dimethylformamide is 1:(3-4).
3. The preparation method according to claim 1 or 2, characterized in that: The heating in step (1) is stirring heating; Preferably, the heating temperature is 90-110°C and the heating time is 12-18 minutes; Preferably, the stirring speed is 500-1000 rpm.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The step (1) is further washed after centrifugation and before drying, wherein the washing comprises: re-dispersing the precipitate obtained after centrifugation in N,N-dimethylformamide and centrifuging for 1-3 times, and then dispersing it in acetone and centrifuging for 2-4 times; Preferably, the centrifugal speed in N,N-dimethylformamide is 8000-12000 rpm, and the centrifugal time is 10-20 min; Preferably, the centrifugal speed in acetone is 9000-13000 rpm, and the centrifugal time is 3-7 min; Preferably, the drying temperature is 70-90°C and the drying time is 10-14h; Preferably, the activation temperature is 100-150° C., and the activation time is 1-3 h.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The metal salt precursor in step (2) includes a nickel salt precursor, a palladium salt precursor, a platinum salt precursor or a ruthenium salt precursor; Preferably, the nickel salt precursor comprises nickel nitrate hexahydrate; Preferably, the mass ratio of the metal salt precursor to the bimetallic organic framework material Ce / Zr-UiO-66 is (1-2):(1-2).
6. The preparation method according to any one of claims 1 to 5, characterized in that: The step (2) of mixing the metal salt precursor with the bimetallic organic framework material Ce / Zr-UiO-66 comprises: dropping the metal salt precursor aqueous solution into the bimetallic organic framework material Ce / Zr-UiO-66 dispersion under stirring; Preferably, the metal salt precursor is mixed with the bimetallic organic framework material Ce / Zr-UiO-66 and stirred for 22-26 hours.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The drying in step (2) includes first evaporating to remove excess water, and then drying; Preferably, the evaporation comprises rotary evaporation; Preferably, the temperature of the rotary evaporation is 50-90°C; Preferably, the rotation speed of the rotary evaporation is 150-200 rpm; Preferably, the rotary evaporation pressure is -0.6 to -1 atm; Preferably, the drying temperature is 60-100° C., and the drying time is 10-14 h.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The reduction in step (2) comprises: heating reduction in an 8%-12% hydrogen atmosphere; Preferably, the heating reduction comprises: heating to 220-280° C. at 1-3° C. / min and reducing for 5-7 hours.
9. A nanocatalyst based on a bimetallic organic framework material obtained according to the preparation method according to any one of claims 1 to 8.
10. Use of the nanocatalyst based on bimetallic organic framework material according to claim 9 in catalyzing CO2 hydrogenation to methane reaction.
Citation Information
Patent Citations
Carbon dioxide methanation catalyst and preparation method thereof
CN117942972A
Nickel-cerium dioxide hollow catalyst as well as preparation method and application thereof
CN118267996A
W modified Ni / gamma-Al2O3 catalyst for methanation of carbon dioxide as well as preparation and application of W modified Ni / gamma-Al2O3 catalyst
CN118719082A
Cited By
Bi (at) Ce-UiO-66-Br catalyst and application of Bi (at) Ce-UiO-66-Br catalyst in photocatalytic reduction of CO2
CN121695952A
A Bi@Ce-UiO-66-Br catalyst and its photocatalytic reduction of CO 2 Application
CN121695952B